Natural Products and teaching in Science: Amazon Tuber as alternative for Acid-Base indicator (Research, Society and Development, 2022)
This paper, describes the analysis of a natural indicator from the tuber of the cara-roxo (Dioscorea trifida), which is a well-known species in the North and Northeast of Brazil. This paper aims to analyse the extract as a natural indicator of acidic and basic substances and to optimize the extraction method. The sample used in the present study was obtained in Coari city, Amazon state. Different extraction parameters were the dry and in natura and the ethanol and hydroalcoholic solvents, all macerated at room temperature. The ability of the extracts to act as an indicator was tested with solutions varying the pH from 1 to 14 and the absorbance in the UV region (300 to 700 nm) was analyzed using a spectrophotometer. The results of this work showed that there was a good efficiency of the extracts as a natural indicator, with characteristic coloration according to the acidity of the medium (acid - lilac, basic – cyber grape and neutral - iris). The dry and crushed hydroalcoholic extract performed better, with a higher wavelength absorption. It is concluded that the purple yam is an alternative to be used in Science classes (Chemistry and Biology), having a simple extraction process, using low cost materials, being a highly reproducible and environment friendly technique, presenting a good performance of color change in different pH solutions, being a possibility of substitution of the traditional indicators, available in the market today.